Pituitary metastasis from renal cell carcinoma: A case report with literature review - Suthinee Ithimakin (2018)
A 52-year-old man suffered from visual disturbance for 5 months. He then developed malaise, constipation and anorexia with significant weight loss. Physical examination showed noticeable signs of hypothyroidism, such as slurred speech, dry skin, macroglossia, myoedema and slow relaxation of ankle reflexes. In addition, eye exam showed abnormal visual acuity with left homonymous hemianopia. A large mass was found at right scapular region. Endocrinologic investigation results were compatible with secondary hypothyroidism with adrenal insufficiency. Subsequent CT brain revealed an enhancing mass at pituitary gland and also a mass at right occipital lobe with surrounding edema. CT of chest demonstrated multiple lung nodules, right scapular mass and incidentally revealed 8.7-cm hypervascular mass at left kidney. The final diagnosis was renal cell carcinoma with bone, lung, brain and pituitary metastasis. He received hormone replacement therapy as well as bisphosphonate and brain radiation. Following treatments, he was able to return to work with recovery of visual impairment. Pituitary metastasis is a rare condition. Our patient presented with symptoms of hypothyroidism which may mimic pituitary adenoma, but had other clues of malignancy such as significant weight loss and scapular mass. The most common cancers that occasionally metastasize to pituitary gland are breast and lung cancer. Previously, renal cell carcinoma with pituitary metastasis has been reported. Unlike our patient, most of these cases developed metachronous pituitary metastasis.